2017
DOI: 10.1021/jacs.7b01480
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Anion Exchange in Cesium Lead Halide Perovskite Nanocrystals

Abstract: Cesium lead halide (CsPbX) perovskite nanocrystals (NCs) possess the unique capability of post-synthesis anion exchange providing facile tunability of the optical properties, which is usually achieved by mixing NCs with reactive anion precursors. In this work, we show that the controllable anion exchange can be achieved in a dihalomethane solution of CsPbX NC in the absence of any spontaneously reacting anion source using photoexcitation of CsPbX NCs as the triggering mechanism for the halide ion exchange. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
208
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(224 citation statements)
references
References 18 publications
15
208
1
Order By: Relevance
“…The conduction band and valence band edge of the CsPbBr 3 NCs is ≈−1.0 and ≈1.5 V versus the normal hydrogen electrode (NHE), respectively. [24] While the conduction band and valence band edge of TiO 2 (anatase) were determined to be ≈−0.5 and ≈2.7 V versus NHE, respectively. [25] Therefore, a type II band alignment with an offset of conduction band (≈−0.5 V) and valence band (≈1.2 V) could form in the CsPbBr 3 /TiO 2 heterostructure.…”
Section: Resultsmentioning
confidence: 99%
“…The conduction band and valence band edge of the CsPbBr 3 NCs is ≈−1.0 and ≈1.5 V versus the normal hydrogen electrode (NHE), respectively. [24] While the conduction band and valence band edge of TiO 2 (anatase) were determined to be ≈−0.5 and ≈2.7 V versus NHE, respectively. [25] Therefore, a type II band alignment with an offset of conduction band (≈−0.5 V) and valence band (≈1.2 V) could form in the CsPbBr 3 /TiO 2 heterostructure.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the large difference in ionic radii between Cl − and I − anions explains why the direct exchange between Cl − and I − anions involves a structural stress on the perovskite lattice, which results in serious degradation of the nanocrystals. Other studies on the halide anion exchange have also been reported, such as halide exchange in solid phase, in the forms of nanorod arrays, nanowires, or nanocubes, photoinduced anion exchange, and gaseous hydrogen halides as the halide precursors …”
Section: Synthesis Challengesmentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence. [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [19,22,[36][37][38][39] In addition, triple-cation (Cs,formamidinium,methylammonium)PbX 3 materials have been developed with the goal of increasing stability while maintaining bright luminescence.…”
Section: Introductionmentioning
confidence: 99%